The internal market and the future of European integration : essays in honour of Laurence W. Gormley / edited by Fabian Amtenbrink, Gareth Davies, Dimitry Kochenov, Justin Lindeboom. - Amtenbrink, Fabian; Davies, Gareth (Barrister); Kochenov, Dimitry, 1979-; Lindeboom, Justin (Cambridge University Press, 2019)
This collection marks the rich legacy of Professor Laurence W. Gormley's scholarship in the field of EU internal market law, providing a definitive critical appraisal of all the key aspects of the internal market, with an emphasis on goods and judicial protection; Professor Gormley's expert fields. Forty chapters deal with constitutional aspects of the EU internal market, the free movement of goods, persons and services, EMU, public procurement and competition law, institutional and procedural dimensions, and the EU's external relations, which includes matters relating to Brexit. The broad theme of the book, reflecting the many interests of Professor Gormley, will appeal to scholars, students and practicing lawyers. Dealing with both classic, foundational aspects of the EU internal market as well as highly topical matters, such as Brexit, this book will be a most welcome addition to every engaged legal scholar's library, thereby celebrating the legacy of a mentor and dear friend.